DESIGNING LEARNING SPACES TO DIFFERENT LEARNING APPROACHES - Aniktar, Serhat; Aytug, Ayfer (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2016)
Over the past two decades, a great deal of research has focused on how people learn. Previously, teaching was most often a kind of broadcast of course content at regularly scheduled intervals, from an expert to student receivers. The learning literature agrees that learning can be enhanced, deepened, and made more meaningful if the curriculum makes the learners active participants through interactivity, multiple roles (such as listener, critic, mentor, presenter), and social engagement (such as group work, discussion boards). Hence, it is no surprise that learning spaces have an increasingly important role in catalyzing this type of learning. There are a lot of learning approaches being applied, such as Montessori, Reggio Emilia, Waldorf, Summerhill. According to these approaches and new technology based approaches, social interactions such as debate, discussion, and teamwork, for example, encourage learning, prompting a design requirement for rooms that can be reconfigured quickly for small discussion groups. If accepted, this principle leads to decisions such as selecting lightweight, wheeled chairs that permit easy reconfiguration of the room's seating. In our country, constructivist learning approach is being applied in primary schools, but learning spaces are not enough for its activities. Classroom design is still based on behavioral approach. In this study, how designing learning spaces to different learning approaches will be comparatively researched by examples. By this study, we can obtain a new perspective and new guide while designing learning spaces.
Keywords: learning; space; design; learning approach; constructivist learning; Education & Educational Research